The genus Xylaria from Maharashtra, India - and R.V. GANDHE*, A.S. KSHIRSAGAR, S.M. RHATWAL (Indian Phytopathology, 2009)
The present paper deals with the ten species of Xylaria collected from Mulashi forest, Western Ghats of Maharashtra, India. These include six new records from India. These are Xylaria beccari, X. cf. brevipes, X. oligotoma, X. schweinitzii, X. scruposa, X. feejeensis (= X. sp. aff. feejeensis). Although some of these species have been previously recorded, present collections showed remarkable morphological differences to the previously described ones.